HUBUNGAN POWER OTOT LENGAN DAN BAHU DAN KELENTUKAN PINGGANG TERHADAP HASIL LEMPAR LEMBING PADA MAHASISWA PUTRA PENJASKESREK ANGKATAN 2014 UNIVERSITAS RIAU - Yuskal Tubet Indra; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The results of field observations indicate the ability of each college student vary in doing the javelin. There are still students who have not the right to do the throws, but there are some students who do throw properly. The purpose of this study was to determine the relationship of power arms and shoulders and waist flexibility to the results of the javelin at the 2014 class of male students Riau University. This type of research is using correlation analysis, survey methods, and population in this study were all students penjaskesrek force in 2014 University of Riau. Sample collection techniques in this study using total sampling. So researchers set of samples in this study were students penjaskesrek force in 2014 as many as 64 people. Results of analysis showed that there is a relationship of power arms and shoulders and waist flexibility to the results of the javelin at the 2014 class of male students of University of Riau, with the count r = 0.836> r table = 0.266Key words : Power arms and shoulders, waist flexibility, javelin .